Reverberations: Polish and Spanish post-transformation prose from a post-dependence perspective - Kłosińska-Nachin, Agnieszka (2022)
The book titled Reverberations. Polish and Spanish post-transformation prose from a post-dependence perspective proposes the adoption of a common research perspective on Polish and Spanish prose written after 1989 and 1975, i.e. since the beginning of the transformation processes in the two countries. This perspective has been suggested by Polish researchers from the circle of post-dependence studies. Post-dependence was developed so as to highlight and understand the condition of subordination that characterises the vast periphery which is Eastern Europe. The author evokes historical and historiographical arguments that justify the possibility of applying the methodology of post-dependence studies to the study of contemporary Spanish culture. An important point of reference for Polish and Spanish culture is the experience of authoritarian rule in the form of Francoism in Spain and communism in Poland. The main part of the book consists of twelve comparative analyses of Polish and Spanish prose, grouped into three thematic blocks: panopticism and violence, capitalism and emancipatory discursive strategies of women. A detailed analysis was conducted on selected works by Antonio Muñoz Molina, Juan José Millás, Andrzej Stasiuk, Tadeusz Konwicki, Marek Nowakowski, Piotr Siemion, Manuel Vázquez Montalbán, Rosa Montero, Carmen Martín Gaite, Montserrat Roig, Izabela Filipiak and Dorota Masłowska. The analyses carried out are, on the one hand, a suggestion to complete the Polish map of post-dependence and, on the other hand, a preliminary recognition of the topography of the Spanish post-dependence discourse.
Keywords: comparative literature; contemporary Polish prose; contemporary Spanish prose; post-dependence studies